Study of land use and land cover in the Mãe Bonifácia State Park in the City of Cuiabá-MT (Research, Society and Development, 2021)
Land use and land cover can be analyzed using the Normalized Difference Vegetation Index (NDVI) and the Earth Surface Temperature (TST). In densely populated areas, the increase in air temperature due to the urban heat island effect can harm the thermal comfort and health of citizens. Urban park is an important criterion to assess the responsibility of the environment in cities, especially those with a tropical climate. In this sense, the present work aimed to study the relationship between land use and land cover, NDVI and TST in the Mãe Bonifácia State Park (PEMB) and its surroundings in the city of Cuiabá, Mato Grosso, in the years 2013 and 2020 with the use of remote sensing techniques and Geographic Information System (GIS). The results showed inverse relationships between the values ​​of NDVI and TST in the period considered, highlighting the microclimatic benefits of the study area. It is thus concluded that there is a relationship between land occupation patterns and the local climate. In this way, planning the administrative management of green areas in cities can optimize the thermal comfort of the population, ensuring a healthy environment.